Three-dimensional simulation of coal catalytic hydrogasification in a pressurized bubbling fluidized bed. (15th December 2021) - Xia, Zihong; Yan, Shuai; Chen, Caixia; Qu, Xuan; Bi, Jicheng
Highlights: A CFD modelling of catalytic hydrogasification is conducted in a pressurized bed. Particles are tracked and simulated during the whole residence time. Small bubbles intensify the transfer process in C-H2 reaction to promote CCHG. Correlation between particle behaviors and CCHG reactivity is revealed. Injection of dispersed H2 is proposed to mediate CCHG performance for scale-up. Abstract: Coal catalytic hydrogasification (CCHG) is an efficient approach to produce CH4 with high yield and high thermal efficiency. A numerical modelling of CCHG in a pressurized bubbling fluidized bed has been conducted to track the whole reaction process by using the multiphase particle-in-cell (MP-PIC) algorithm during the residence time of particles. The gas–solid flow dynamic properties, such as bubble size and bed expansion height, were validated against with empirical correlations. After incorporating the CCHG kinetics with MP-PIC, the simulated bed temperature, gaseous compositions, and CH4 formation behavior were verified with the experimental data. The trajectory and physiochemical properties of char particles (particle diameter, temperature, heat transfer coefficient and drag function) during the whole residence time were explored comprehensively. The results showed that a high temperature region appeared in the dense bed located 20–30 mm above the plate distributor initially, which led to the profound fluidization performance and reactivity of char particles with diameter range of 138–249 μm. With the CCHG proceeding, particle diameter decreased gradually, while the heat transfer coefficient and drag force were strengthened. A uniform bed temperature was generated afterwards resulted by the enhanced gas-particle heat transfer. Whereas, when the particle diameter decreased to less than 46 μm, char particles were blown out of the dense bed, resulting in the low reactivity and difficulty of separation for the practical application. The numerical results in this work shed light on further scaling up and design of pressurized fluidized bed for coal catalytic hydrogasification.